High-redshift radio galaxies: a potential new source of 21-cm fluctuations. Issue 4 (21st October 2020) - Reis, Itamar; Fialkov, Anastasia; Barkana, Rennan
ABSTRACT: Radio sources are expected to have formed at high redshifts, producing an excess radiation background above the cosmic microwave background (CMB) at low frequencies. Their effect on the redshifted 21-cm signal of neutral hydrogen is usually neglected, as it is assumed that the associated background is small. Recently, an excess radio background has been proposed as a possible explanation for the unusually strong 21-cm signal reported by EDGES. As a result, the implications of a smooth and extremely strong excess radio background on both the sky-averaged 21-cm signal and its fluctuations have been considered. Here, we take into account the inhomogeneity of the radio background created by a population of high-redshift galaxies and show that it adds a new type of 21-cm fluctuations to the well-known contributions of density, velocity, Ly α coupling, heating, and reionization. We find that a population of high-redshift galaxies even with a moderately enhanced radio efficiency (unrelated to the EDGES result) can have a significant effect on the 21-cm power spectrum and global signal. For models that can explain the EDGES data, we show that the 21-cm power spectrum at z ∼ 17 is enhanced by up to two orders of magnitude compared to the CMB-only standard case, with a significantly modified shape and time evolution due to radio fluctuations. These fluctuations are within reach of upcoming radio interferometers. We also find that these models can be significantly constrained by current and future observations of radio sources.